Domain-specific application frameworks: Framworks experience by industry (New York, 1999)
This book contains real samples of computer-integration manufacturing frameworks, distributed systems frameworks, networking and telecommunication application frameworks, and systems development environment framworks.
Keywords: application software - development,computer software - reusability,object-oriented programming ( computer science )